Pendekatan Feminis Dekonstruktif-Kultural terhadap Anna and the King - Ratna Asmarani (KAJIAN SASTRA, 2008)
This paper focuses on analyzing the novel entitled Anna and the King using the feminist cultural deconstructive approach. The purposes to dig out the hidden meaning contained in the novel through deconstructive approach from a feminist perspective about two different cultures (British and Siam) that interact for a long time. The result shours that each side -Anna the British woman and King Maha Mongkut of Siam- deconstructs and is deconstructed in the process of interaction. Both, in the long run, have a blend of cultures for their own betterment and for the betterment of the people around them.